Interpolation and mapping of the total electron content over the Malaysian region - Lim, Wen Hong (2008)
In the vast areas of satellite-related applications, the ionosphere is the main cause of error due to the Total Electron Content (TEC), which causes the ionospheric delay. As a result, estimating and mapping the TEC is vital for the application of various satellite-related fields, which are gaining momentum in Malaysia. Thus, this study aims to develop an efficient approach in mapping the TEC over Malaysian region using interpolation method. The TEC was mapped using three interpolation methods, namely inverse distance weighting (IDW), multiquadric and sphere multiquadric for different size of study area, different distribution and quantity of reference points. All the results from these three methods were compared with the TEC derived from IRI-2001 model and calculated for the root mean square (RMS) values. This study found that the effects of the quantity and distribution of reference points were conspicuous in the results obtained via both multiquadric and sphere multiquadric methods, whereas IDW was not conspicuously affected by both factors. This can be seen from the RMS values obtained from the IDW for both the well-distributed and randomly distributed two reference points were 3.1894 and 6.1681, whereas for the 18 reference points, the RMS yielded were 2.2436 and 2.5748 respectively. Furthermore, the results, especially via the multiquadric and IDW methods were more accurate in smaller study area’s size, where the RMS yielded were 0.4685 and 0.0649 respectively for the 1º x 1º area size. However, IDW seemed to consistently generate the more accurate result for all the study area size, where the RMS generated for all the area sizes studied ranges from 0.0649 to 1.2178. As a conclusion, the IDW method is the most suitable interpolation for the Malaysian region.